THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE AND THE GOVERNMENT’S INTERNAL CONTROL SYSTEM IN EFFORT TO IMPROVE THE QUALITY OF REGIONAL FINANCIAL REPORTS IN PALEMBANG CITY - Leriza Desitama Anggraini; Andini Utari Putri (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
The implementation of good corporate governance should be supervised and controlled both internally and externally so that the quality of LKPD can be guaranteed. SPIP also has a role in controlling which has the impact of the presentation of quality financial reports. This study aims to find out how much the implementation of good corporate governance and the government's internal control system is to improve the quality of regional financial reports in Palembang City. This study used a sample of 58 respondents in the Regional Financial and Asset Management Agency (BPKAD) Palembang City. The research method uses descriptive quantitative methods using statistical calculations with SPSS as an analytical tool. In this study, descriptive statistics were used along with reliability, validity, and traditional assumption tests (like the tests for normality, multicollinearity, autocorrelation, and heteroscedasticity), multiple linear regression analysis, and hypothesis testing (like the simultaneous test, partial test, and test of the coefficient of determination). The study's findings indicate that both effective corporate governance and internal control systems have a favourable impact on the accuracy of financial reports. The independent variables of sound corporate governance and an effective internal control system are concurrently positive and significant to the independent variable, which is the calibre of financial reports, according to the statistical test F.Keywords: Governance, Internal Control, Financial Statements